![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
(2x + 1)3 = 125 = 53
=> 2x + 1 = 5
2x = 5 - 1
2x = 4
x = 4:2
x = 2
![](https://rs.olm.vn/images/avt/0.png?1311)
\(5^{2x+1}=125\)
\(\Rightarrow5^{2x+1}=5^3\)
\(\Rightarrow2x+1=5\)
\(\Rightarrow2x=4\)
\(\Rightarrow x=2\)
\(5^{2x+1}=125\)
\(\Rightarrow5^{2x+1}=5^3\)
\(\Rightarrow2x+1=5\)
\(\Rightarrow2x=5-1\)
\(\Rightarrow2x=4\)
\(\Rightarrow x=4:2\)
\(\Rightarrow x=2\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\left(2x+1\right)^3=125\)
\(\left(2x+1\right)^3=5^3\)
\(2x+1=5\)
\(2x=5-1\)
2x=4
x=4/2
x=2
\(\left(4x-1\right)^2=25\cdot9\)
\(\left(4x-1\right)^2=225\)
\(\left(4x-1\right)^2=15^2\)
\(4x-1=15\)
4x=15+1
4x=16
x=16/4
x=4
![](https://rs.olm.vn/images/avt/0.png?1311)
a)\(\left(2x+1\right)^3=5^3\)
\(\Rightarrow2x+1=5\)
\(2x=5-1\)
\(2x=4\)
\(x=4:2\)
\(x=2\)
\(b,\left(2x-1\right)^3=125\)
\(\Rightarrow2x-1=5\)
\(2x=5+1\)
\(2x=6\)
\(x=6:2=3\)
b) \(\left(2x-1\right)^3=125\)
\(\left(2x-1\right)^3=5^3\)
\(2x-1=5\)
\(2x=5+1\)
\(2x=6\)
\(x=6:2\)
\(x=3\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a)Câu a sai đề
b)x=4
k mik nha
Học tốt
viết lại đề câu a nha
![](https://rs.olm.vn/images/avt/0.png?1311)
a) x10 = 1x
=> x10 = 1
=> x10 = 110 => x = 1
b) x10 = x
=> x10 - x = 0
=> x(x9 - 1) = 0
=> \(\orbr{\begin{cases}x=0\\x^9-1=0\end{cases}}\Rightarrow\orbr{\begin{cases}x=0\\x=1\end{cases}}\)
c) x5 = 32 => x5 = 25 => x = 2
d) 3x = 81 => 3x = 34 => x = 4
e) 25x = 1252
=> 25x = (53)2
=> (52)x = 56
=> 52x = 56
=> 2x = 6 => x = 3
f) (2x - 15)5 = (2x - 15)3
=> (2x - 15)5 - (2x - 15)3 = 0
=> (2x - 15)3 [(2x - 15)2 - 1] = 0
=> \(\orbr{\begin{cases}\left(2x-15\right)^3=0\\\left(2x-15\right)^2-1=0\end{cases}}\)
=> \(\orbr{\begin{cases}2x-15=0\\\left(2x-15\right)^2=1\end{cases}\Rightarrow}\orbr{\begin{cases}x=\frac{15}{2}\\\left(2x-15\right)^2=\left(\pm1\right)^2\end{cases}}\)
+) 2x - 15 = 1 => 2x = 16 => x = 8
+) 2x - 15 = -1 => 2x = 14 => x = 7
Vậy x = 8,x = 7
![](https://rs.olm.vn/images/avt/0.png?1311)
(2x+1)^3=125
=> (2x + 1 )^3 = 5^3
=> 2x + 1 = 5
=> 2x = 5 - 1
=> 2x = 4
=> x = 4 : 2
=> x = 2